New Applications in Gas Geochemistry. (2nd July 2020) - Italiano, Francesco; Solecki, Andrzej; Martinelli, Giovanni; Wang, Yunpeng; Zheng, Guodong
Abstract : Gases present in the Earth crust are important in various branches of human activities. Hydrocarbons are a significant energy resource, helium is applied in many high-tech instruments, and studies of crustal gas dynamics provide insight in the geodynamic processes and help monitor seismic and volcanic hazards. Quantitative analysis of methane and CO2 migration is important for climate change studies. Some of them are toxic (H2 S, CO2, CO); radon is responsible for the major part of human radiation dose. The development of analytical techniques in gas geochemistry creates opportunities of applying this science in numerous fields. Noble gases, hydrocarbons, CO2, N2, H2, CO, and Hg vapor are measured by advanced methods in various environments and matrices including fluid inclusions. Following the "Geochemical Applications of Noble Gases"(2009), "Frontiers in Gas Geochemistry" (2013), and "Progress in the Application of Gas Geochemistry to Geothermal, Tectonic and Magmatic Studies" (2017) published as special issues of Chemical Geology and "Gas geochemistry: From conventional to unconventional domains" (2018) published as a special issue of Marine and Petroleum Geology, this volume continues the tradition of publishing papers reflecting the diversity in scope and application of gas geochemistry.